2000
DOI: 10.1080/00102200008935790
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Radiant Heat Attenuation Through Water Mist

Abstract: This paper describes the development of a two-phase radiation model for the prediction of radiant heat attenuation in fires by water mist. It has been especially developed for incorporation in comprehensive field models of fire extinguishment by a water mist. The model predicts the opacity of the mist by summing over the absorption and scattering coefficients for each panicle size present. A novel approach is proposed to reconcile the Eulerian fonn of the radiation transport equations with the Lagrangian parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Nevertheless, it may be useful to develop an approximate transmissivity, which may be used qualitatively to assess the attenuation effectiveness of a mist. Moreover, such numbers provide a means to compare with earlier analyses (e.g., [12,13]) that report transmissivity, but do not consider in-scattering effects. For the purposes of comparing with the results of Ravigururajan [12], the transmissivity here is defined as the remaining total radiative energy at 3 m into a mist divided by the initial radiative energy.…”
Section: Transmissivitymentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, it may be useful to develop an approximate transmissivity, which may be used qualitatively to assess the attenuation effectiveness of a mist. Moreover, such numbers provide a means to compare with earlier analyses (e.g., [12,13]) that report transmissivity, but do not consider in-scattering effects. For the purposes of comparing with the results of Ravigururajan [12], the transmissivity here is defined as the remaining total radiative energy at 3 m into a mist divided by the initial radiative energy.…”
Section: Transmissivitymentioning
confidence: 95%
“…They reported that the maximum attenuation is achieved when droplet radius is equal to the wavelength. In another study, Keramida et al [13] developed a twophase model to predict the radiation attenuation by water mist. Their model was developed to be incorporated into a multidimensional model for fire extinction by water mist.…”
Section: Radiation Attenuation and Flame Interactionsmentioning
confidence: 98%
“…For example, Ravigururajan et al [11] modeled radiation absorption by water droplets using Lambert-Beer's law and determined spectral attenuation factors. In another study, Keramida et al [12] developed a two-phase model to predict radiation attenuation by water mists. In more recent studies [13,14], the effects of droplet diameter and number density have been investigated to determine the structure and extinction of premixed, freely propagating, stoichiometric, methane-air flames.…”
Section: Radiative Transfer In a Water Spray Polydispersionmentioning
confidence: 98%
“…The effect of water droplets on the suppression of fire and as a shielding mechanism has been the subject of many studies [7][8][9][10][11][12][13][14][15][16][17]. Kermida [7] found the ability of water droplets to suppress fires is due to the following four methods; gas phase cooling, oxygen dilution, fuel bed cooling, and radiation attenuation. This study utilized the ability of water to attenuate radiation to reduce the heat flux leaving the compartment.…”
Section: Introductionmentioning
confidence: 99%
“…This study utilized the ability of water to attenuate radiation to reduce the heat flux leaving the compartment. The main mechanisms involved are radiation absorption and scattering by water droplets [7][8][9][10][11][12][13]. Chow [14] and Choi [15] performed similar experiments in order to determine if a room could be protected from a fire in an adjacent room with the use of a water curtain.…”
Section: Introductionmentioning
confidence: 99%